Mündlichkeit als threshold concept – metasprachliche Hinweise auf eine wissenschafts-/fachdidaktische Herausforderung - Sacher, Julia (Zeitschrift für angewandte Linguistik : ZfAL, 2025)
Research into the characteristics of spoken language has been a core component of linguistics for many years and has led to the realisation that oral and written language have different functions and purposes. This knowledge is crucial for (prospective) German teachers. However, empirical data from small student groups working on data of classroom interaction show that students often appear to analyse these data based on written language norms. This can be reconstructed by analysing the students‘ metapragmatic statements. The article suggests that valuable insights into issues relevant to the acquisition of subject-specific concepts can be gained from the analysis of these statements. From this professionalisation-oriented perspective on tertiary learning, the linguistic concept on orality can be understood as a threshold concept that is difficult for students to grasp due to their written language bias.